LITERASI DERADIKALISASI DIBALIK KASUS RADIKALISME "PERISTIWA PENUSUKAN MENKOPOLHUKAM WIRANTO DI PANDEGLANG, BANTEN" - Rully Khairul Anwar (Brawijaya Journal of Social Science, 2020)
Deradicalization literacy is the ability and knowledge of individuals to be able to search, manage and use information that has been obtained in an effort to evaluate the information about the ideology of radicalism they receive. The ability of deradicalization literacy must be possessed by every individual in the case of radicalism is a serious problem and is a cruel act of violence and a form of betrayal against the government. The purpose of this study is to find out how the concept of deradicalization literacy can be applied in studying the radicalism event "The Stabbing of MENKOPOLHUKAM Mr.Wiranto, Menes Pandeglang Banten". The method used in this research is descriptive qualitative approach to literature study. The results of this study are the deradicalization literacy is the first step in fighting the ideology of radicalism and all elements of society have an active role in doing so to maintain the integrity of the life of the nation and state.Keywords: Radicalism, Deradicalism Literacy, Religion, Nationalism, Citizenship Education